Exposure to the World Trade Center disaster and test performance among New York City public school students over time, 1998–2003 - Erin Takemoto; Sean Locke; Dana E. Goin; Joan A. Casey; Ingrid Giesinger; Mark Farfel; Howard Alper; Robert Brackbill (SSM - Mental Health, 2022)
Background: The World Trade Center (WTC) disaster exposed children to environmental toxins and emotional traumas. WTC exposure health effects have been well-documented; impacts on education outcomes, which have been associated with health over the life course, have not. We examined the WTC disaster's impact on math and English language arts (ELA) exams among New York City (NYC) public school students. Methods: Student-level data for 3rd graders in 1998–99 were obtained for five consecutive school years, three pre-9/11 and two post-9/11 from the NYC Department of Education. Piecewise linear mixed models with two slopes representing two time periods—pre-and post-9/11—were used to examine the WTC impact on exam scores among 393 students in exposed Ground Zero area schools (WTC site: 0–1.5 miles) versus 39,047 students in unexposed NYC schools (WTC site: >6 miles). Results: On math exams, students in Ground Zero area schools were improving their scores in both the pre-9/11 period and post-9/11 period – with a slightly greater magnitude of improvement post-9/11 (change in slope post-9/11 from pre-9/11: 0.5, 95% CI: 3.1, 5.2). Students in unexposed schools experienced a slight decrease in the rate of improvement on math scores in the post-9/11 period (change in slope post-9/11 from pre-9/11: 0.6, 95% CI: 1.2, −0.0). On ELA exams, both students in Ground Zero area schools and unexposed schools were positively increasing their test scores in both the pre-9/11 and post-9/11 period; both groups experienced a faster rate of improvement in the post-9/11 period (change in slope post-9/11 from pre-9/11 [95% CI]: Ground Zero: 1.2 [-2-2, 4.5], unexposed: 3.0 [2.6, 3.4]. Conclusions: Compared to the pre-9/11 time-period, students in Ground Zero area schools experienced modest improvements in test scores in the post-9/11 time-period. Futures studies should evaluate long-term impacts on education, as outcomes may differ compared to the short-term effects.